VP192 Importance Of Contextual Data In Producing Health Technology Assessment Recommendations. (12th January 2018) - Bellemare, Christian; Poder, Thomas
Abstract : INTRODUCTION: Available data in the scientific literature is not always sufficient to make a clear Health Technology Assessment (HTA) recommendation without any other source of data. Contextual data and local expertize are an important source of data that cannot be ignored in HTA process. Despite a lack of evidence in the scientific literature, a technology can be recommended in a given context. We illustrate this by a case study about biplane angiography for vascular neurointervention. METHODS: A systematic review was conducted. The level of evidence was assessed by the grid of Downs and Black. An analysis of the context in our setting was also conducted. The main outcomes were: radiation doses, clinical complications, procedure times, purchase cost, impact on teaching programs, confidence of clinicians in the technology, quality of care, and volume of activity. A committee constituted of managers, clinical experts, physicians, physicists and HTA experts was created to produce a recommendation about biplane technology acquisition. RESULTS: A list of 257 citations was obtained yielding 9 eligible articles for analysis. Despite the lack of evidence found in the literature (median of Downs and Black: 3/32), the biplane system appears to reduce ionizing radiation and medical complications as well as shorten procedure time. Contextual data indicated that biplane system could improve operator's confidence, which could translate into reduced risk, especially for complex procedures. We estimate that a minimum of 50 cases can be done in our context (University hospital center covering a population of 306, 322 people) with a higher level of patient safety. In addition, the biplane system can support our institution in advanced procedures teaching program. CONCLUSIONS: Given on the advantages provided by the biplane technology in our setting, the committee has recommended its acquisition. However, this technology should be implemented with a responsibility in collecting outcome data to optimize clinical protocol in doses of ionizing delivered.